Psychometric Properties of Revised Illness Perception Questionnaire: Testing on Patients with Breast Cancer and Ischemic Heart Disease - Yaltonsky V.; Moskovchenko D.; Sirota N.; Yaltonskaya A.V. (Клиническая и специальная психология, 2017)
The article presents result of testing revised illness perception questionnaire. The questionnaire was developed based on the model of self-regulation G. Leventhal. The study involved 140 patients: patients with breast cancer and patients with ischemic heart disease. It is shown that the Russian version of revised illness perception questionnaire is a reliable tool for quantifying components of the perception of the disease. The technique has sufficient reliability, performance consistency and internal structure corresponds to the English version. External validity questionnaire confirmed significant association components of illness perception with personal anxiety. According to the results of cluster analysis questionnaire scales was isolated polar continuum of possible options for responding to the disease, manifested in specific types of attitude to the disease.